Effect of the thumbtack needle on gastrointestinal function recovery after laparoscopic radical gastrectomy for gastric cancer with the concept of enhanced recovery after surgery: a randomized controlled trial - Guo, Shuai; Lin, Xiang-Ping; Jin, Xiang-Ren; Tuo, Kang-Xiu; Li, Pei; Yang, Wei-Wei; Wang, Qian (Frontiers in Surgery, 2025)
ObjectivesPostoperative gastrointestinal (GI) dysfunction is a common complication in patients undergoing gastric cancer surgery. This study aimed to evaluate the effect of thumbtack needle therapy on GI function recovery after laparoscopic radical gastrectomy.MethodsParticipants were randomly assigned to either the treatment or control group. Both groups received perioperative enhanced recovery after surgery management. Participants in the treatment group received thumbtack needle therapy at bilateral Neiguan (PC6), Zusanli (ST36), Shangjuxu (ST37), Hegu (LI4), and Sanyinjiao (SP6). Primary outcomes included the time to bowel sound recovery and time to first flatus (all measured in hours). Secondary outcomes included the time to first defecation, time to removal of the nasogastric tube and intra-abdominal drains (all measured in hours), postoperative pain scores, nausea and vomiting scores, abdominal distension scores (all measured in points), length of hospital stay (days), incidence of complications (%), safety evaluation, and overall response rate (%).ResultsA total of 103 participants were screened, and 80 were enrolled (40 per group). Baseline characteristics were similar between groups. Compared with the control group, the treatment group showed significantly shorter times to bowel sound recovery (difference, −4.0 h, 95% CI: −7.0 to −1.0, P = 0.010), first flatus (−11.0 h, 95% CI: −19.0 to −2.0, P = 0.017), first defecation (−8.0 h, 95% CI: −16.0 to −1.0, P = 0.026), nasogastric tube removal (−12.0 h, 95% CI: −27.0 to −2.0 P = 0.023), and intra-abdominal drain removal (−10.0 h, 95% CI: −21.0 to −1.0, P = 0.038). Pain scores were significantly lower in the treatment group on postoperative day (POD) 1 (−1, 95% CI: −1 to 0, P = 0.031), POD 2 (−1, 95% CI: −2 to −1, P < 0.001), and POD 3 (−1, 95% CI: −2 to 0, P < 0.001). Similar improvements were observed in nausea, vomiting, and abdominal distension scores on POD 1–3 (all showing a median difference of −1, all P < 0.05). The treatment group also had a significantly shorter hospital stay (difference, −1.7 days, 95% CI: −3.0 to −0.3, P = 0.015). There was no significant difference in the incidence of postoperative complications (difference, −5.0%, 95% CI: −18.6 to 8.0, P = 0.396), and no adverse reactions occurred in the treatment group. The overall response rate was significantly higher in the treatment group (difference, 17.5%, 95% CI: 0.18–34.0, P = 0.046).ConclusionThumbtack needle therapy at bilateral Neiguan (PC6), Zusanli (ST36), Shangjuxu (ST37), Hegu (LI4), and Sanyinjiao (SP6) is a safe and effective intervention that promotes early recovery of GI function after laparoscopic radical gastrectomy for gastric cancer.Clinical Trial Registrationhttp://www.chictr.org.cn, ChiCTR2400084712.